The introduction of the fungal d-galacturonate pathway enables the consumption of d-galacturonic acid by Saccharomyces cerevisiae. Issue 1 (December 2016) - Biz, Alessandra; Sugai-Guérios, Maura; Kuivanen, Joosu; Maaheimo, Hannu; Krieger, Nadia; Mitchell, David; Richard, Peter
Abstract Background Pectin-rich wastes, such as citrus pulp and sugar beet pulp, are produced in considerable amounts by the juice and sugar industry and could be used as raw materials for biorefineries. One possible process in such biorefineries is the hydrolysis of these wastes and the subsequent production of ethanol. However, the ethanol-producing organism of choice, Saccharomyces cerevisiae, is not able to catabolized -galacturonic acid, which represents a considerable amount of the sugars in the hydrolysate, namely, 18 % (w/w) from citrus pulp and 16 % (w/w) sugar beet pulp. Results In the current work, we describe the construction of a strain ofS. cerevisiae in which the five genes of the fungal reductive pathway ford -galacturonic acid catabolism were integrated into the yeast chromosomes:gaa A, gaa C andgaa D fromAspergillus niger andlgd 1 fromTrichoderma reesei, and the recently describedd -galacturonic acid transporter protein, gat 1, fromNeurospora crassa . This strain metabolizedd -galacturonic acid in a medium containingd -fructose as co-substrate. Conclusion This work is the first demonstration of the expression of a functional heterologous pathway ford -galacturonic acid catabolism inSaccharomyces cerevisiae . It is a preliminary step for engineering a yeast strain for the fermentation of pectin-rich substrates to ethanol.